STABILIZING THE SURFACE pH OF ZINC FOIL USING A FUNCTIONAL ELECTROLYTE STRICTION
By introducing D-galactose into the zinc salt electrolyte, adjusting the pH value of the zinc anode and forming a solvated shell layer, the problems of dendrites of zinc anode are solved, and the high stable cycle and long life of zinc ion batteries are achieved.
Patent Information
- Application Number
- CN202411409721.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-10
- Publication Date
- 2024-12-31
AI Technical Summary
The zinc metal anode has serious dendrite growth and corrosion problems, which affects the cycling stability and efficiency of zinc ion batteries. The existing technology has failed to effectively adjust the pH environment on the surface of zinc anode.
D-galactose (D-Gal) is introduced as an additive in zinc salt electrolyte to adjust the surface pH of the zinc anode, and by forming a solvated shell layer and physical barrier, inhibiting the interaction between zinc and water, and improving the stability of zinc anode .
The 2600-hour stable cycle of zinc||Zn symmetrical battery and the 2000-round stable operation of ZnxV2O5-H2O full battery under 1 A g-1 condition were achieved, which significantly improved the stability and circulation performance of zinc anode.
Smart Images

Figure CN119230973A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the field of electrochemical energy storage, and in particular to the preparation of electrolytes for long-cycle corrosion-resistant aqueous zinc ion batteries and applications of the batteries. Background Art
[0002] With the development of smart electronic devices, electric vehicles, large-scale energy storage and other fields, people have higher and higher requirements on the energy density, fast charging and discharging performance and safety performance of energy storage devices. As a cost-effective and safe energy device, zinc is abundant in resources, low in cost, high in safety and has a high theoretical specific capacity (820 mAh g -1 ), therefore, zinc-ion batteries have greater development prospects and are expected to be widely used in large-scale energy storage devices.
[0003] However, zinc metal anodes have inherent problems such as severe dendrite growth, zinc corrosion in mild electrolytes, and hydrogen evolution reaction (HER), which seriously affect the coulombic efficiency and cycle stability of zinc metal batteries. It has been reported that various strategies to inhibit zinc dendrite growth and corrosion include surface coating, separator modification, functionalized gel electrolyte, anode structure design, and introduction of electrolyte additives. The introduction of suitable additives into traditional zinc salts can change the solvent sheath structure of zinc ions and is a simple and effective method to stabilize the chemical properties of metallic zinc. Some additives such as thiourea, zinc gluconate, sodium glutamate, lignin, and diammonium phosphate have been widely reported. Constructing a sustainable and stable zinc / electrolyte interface and regulating Zn 2+ Solvation structure, homogenization of Zn 2+ Increasing flux, reducing water activity, and inhibiting the occurrence of parasitic reactions are effective strategies to improve the performance of metallic zinc anodes, while directly adjusting the interfacial pH environment has not received due attention.
[0004] The zinc ion is surrounded by six water molecules. During the zinc deposition process, the active water molecules are stimulated by electrons, which weakens the hydrogen bonds and forms OH - and increase the pH value of the interface. Organic solvents have a stronger effect on Zn than water molecules. 2+ The chemical affinity of Zn||Zn is stronger, and the solvent molecules can be removed from the interface by using organic solvents. To this end, we introduced a new environmentally friendly additive, D-galactose (D-Gal), into the ZnSO4 electrolyte system. The purpose is to improve the performance of the zinc anode by pH adjustment. Thanks to the protection of the D-Gal layer, the Zn||Zn symmetric battery performs well at a current density of 1 mA cm -2 Under the condition of 2600 hours, Zn x V2O5-H2O (ZVO) full cell at 1 A g -1 Under the condition of stable operation, it can work more than 2000 times. Summary of the invention
[0005] The present invention is mainly suitable for the preparation of electrolytes for aqueous zinc ion batteries with long cycle and high stability. The introduction of D-Gal can expand the solvation shell of Zn2⁺, reduce the interaction between Zn2⁺ and H2O, balance the surface pH value of zinc anode, and effectively improve the stability of zinc negative electrode. By adding some D-Gal to zinc salt, a stable cycle of 2600 hours of Zn||Zn symmetrical battery can be achieved. x V2O5-H2O (ZVO) full cell at 1 A g -1 It can work stably for more than 2000 cycles under the conditions.
[0006] To achieve the above objectives, the present invention adopts the following technical solutions:
[0007] The aqueous zinc ion battery electrolyte is mainly composed of zinc salt, organic solvent and water, wherein the molar concentration of the organic solvent is D-Gal is 0-0.5 mol / L.
[0008] Based on the above scheme, preferably, the zinc salt is zinc sulfate, zinc chloride, zinc nitrate, zinc acetate, zinc phosphate,
[0009] Any of zinc fluoromethanesulfonate, zinc bis(trifluoromethanesulfonyl)imide, zinc tetrafluoroborate, zinc hexafluorophosphate, zinc bis(oxalate)borate
[0010] The invention further preferably comprises one or a combination of at least two of them, and zinc sulfate is further preferred.
[0011] Based on the above scheme, the organic solvent additive is monosaccharide.
[0012] Based on the above scheme, preferably, the monosaccharide is one or a combination of at least two of glucose, fructose and galactose, and more preferably D-galactose.
[0013] The concentration of the electrolyte salt is 0 M to 15 M, where M is the mass concentration, that is, the ratio of the number of moles of the electrolyte salt to the mass of the solvent: mol kg -1 .
[0014] Based on the above scheme, preferably, the zinc salt concentration is 0.1-2.5 mol kg -1 (M), more preferably 2 M.
[0015] Based on the above scheme, preferably, the content of D-Gal in the mixed electrolyte is 0-0.5 M, and the low-temperature aqueous ion battery electrolyte is specifically D-Gal-10, D-Gal-50, D-Gal-0.2, and D-Gal-0.5.
[0016] Based on the above scheme, preferably, the zinc ion battery is composed of a positive electrode, a membrane and a zinc negative electrode material. The positive electrode is a zinc ion insertion and extraction type material, and the manganese-based material is MnO2, Ca 0.28 The vanadium-based material is one or more of V2O5, V2O3, Zn2V2O7 and KV3O8; the membrane is a glass fiber membrane or a Celgard membrane; the zinc negative electrode is zinc foil or zinc powder.
[0017] The present invention also provides application of aqueous ion battery electrolyte in aqueous ion battery.
[0018] Innovation
[0019] Using D-Gal-doped electrolyte as a functional electrolyte, the Zn 2+ Solvation structure, in addition, the chemical adsorption of D-Gal on the Zn anode (-0.98 eV) can control the Zn 2+ flux and forms a physical barrier at the atomic level, isolating the metallic Zn anode from the aqueous environment, isolating H2O from contact and anchoring the Zn 2+ The higher HOMO energy level makes D-Gal preferentially decompose into lactic acid on the surface of zinc anode, thus stabilizing the pH value on the surface of zinc anode. The stable cycle of Zn||Zn symmetric battery for 2600 hours is achieved. x V2O5-H2O (ZVO) full cell at 1 A g -1 It can work stably for more than 2000 cycles under the condition of
[0020] Beneficial effects of the present invention:
[0021] The present invention innovatively studies the method of adding D-Gal to the ZnSO4 electrolyte on the surface of the Zn anode to stabilize the pH value. The addition of D-Gal improves the 2+ The solvation structure of D-Gal can stabilize the interfacial pH during the cycle, which is beneficial to the uniform deposition of Zn, reduces the interfacial energy, and regulates the uniform zinc plating process. The addition of D-Gal not only achieves highly reversible zinc plating / stripping behavior with a CE of up to 99.7% in the Zn||Cu half-cell, but also after 2000 cycles, the Zn||ZVO battery has a high conductivity at 1.0 A g -1 Under the condition of , there is still a capacity retention rate of 62.78%. BRIEF DESCRIPTION OF THE DRAWINGS
[0022] Figure 1 : Zn in D-Gal-0.2 electrolyte in Example 1 2+ Schematic diagram of the solvation structure.
[0023] Figure 2: Fitted CIP and SSIP diagrams in different electrolytes in Example 2.
[0024] Figure 3 : The various electrolytes in Example 3 1 H NMR spectroscopy.
[0025] Figure 4 : CA curves of ZS and D-Gal-0.2 electrolyte in Zn||Zn battery in Example 4, with a constant potential of -150mV.
[0026] Figure 5 : Linear polarization curves in ZS and D-Gal-0.2 electrolytes in Example 5.
[0027] Figure 6 : In situ pH diagram of ZS electrolyte in zinc symmetric battery in Example 6.
[0028] Figure 7 : In situ pH diagram of D-Gal electrolyte in zinc symmetric battery in Example 6.
[0029] Figure 8 : HOMO diagram of H2O and D-Gal in Example 7
[0030] Fig. 9 : EIS graphs of different electrolytes in Example 8.
[0031] Fig.10 : XRD pattern of zinc anode after 25 cycles in Example 9.
[0032] Fig.11 : Zn anode in a) ZS electrolyte and b) D-Gal-0.2 electrolyte at 10 mA cm -2 In situ optical microscopy images.
[0033] Fig.12 : In Example 11, different electrolytes at 2 mA cm -2 and 1 mAh cm -2 Coulombic efficiency diagram of Zn||Cu battery under conditions.
[0034] Fig.13 : In Example 12, different electrolytes at 1 mA cm -2 and 1 mAh cm -2 Cycling stability of Zn||Zn symmetric batteries using different electrolytes under different conditions.
[0035] Fig.14 : In Example 13, the Zn||ZVO soft pack battery is at 1 A g -1 Cycling performance under 400 nm. (Inset shows the soft pack voltage curve). DETAILED DESCRIPTION
[0036] The following examples are provided to further illustrate the present invention, but are not intended to limit the scope of the present invention.
[0037] Embodiment 1:
[0038] Prepare 2 M zinc sulfate electrolyte (ZS)
[0039] Prepare a mixed electrolyte solution containing 2 M zinc sulfate and 10 mM D-galactose (D-Gal-10).
[0040] Prepare a mixed electrolyte solution containing 2 M zinc sulfate and 50 mM D-galactose (D-Gal-50).
[0041] A mixed electrolyte solution containing 2 M zinc sulfate and 0.2 M D-galactose (D-Gal-0.2) was prepared.
[0042] A mixed electrolyte solution containing 2 M zinc sulfate and 0.5 M D-galactose (D-Gal-0.5) was prepared.
[0043] A schematic diagram is used to illustrate the effect of the addition of D-Gal on the solvation structure of ZS. The results are shown in Figure 1 The zinc ions in ZS dissolution are mainly composed of two components: solvent separated ion pairs (SSIP) and contact ion pairs (CIP). The schematic diagram of D-Gal-0.2 solution shows that the content of solvated water is suppressed.
[0044] Embodiment 2:
[0045] For the ZS, D-Gal-10, D-Gal-50, D-Gal-0.2 and D-Gal-0.5 electrolytes in Example 1, Raman spectra were measured and fitted into CIP and SSIP graphs.
[0046] Test results see Figure 2 The content of SSIP in D-Gal-0.2 electrolyte is the highest, and the content of CIP is the lowest, indicating that the content of solvated water is reduced.
[0047] Embodiment 3:
[0048] The ZS, D-Gal-10, D-Gal-50, D-Gal-0.2 and D-Gal-0.5 electrolytes in Example 1 were tested. 1 H NMR spectroscopy.
[0049] Test results see Figure 3 After adding D-Gal, 1The H peak shifted from 3.732 ppm to the high field direction and reached 3.913 ppm in the electrolyte containing 0.2 M D-Gal. D-Gal molecules can interact with free H2O molecules to form weak hydrogen bonds (O─H─O), which may destroy the initial HB network between H2O and thus reduce the activity of H2O. In other words, inducing H2O decomposition usually requires higher overpotential and more energy.
[0050] Embodiment 4:
[0051] ZS and D-Gal-0.2 electrolyte in Example 1.
[0052] Test results see Figure 4 The Zn 2+ Surface diffusion behavior during deposition. In the ZS electrolyte, the current continued to increase within 100 seconds, indicating that the planar 2D diffusion process was very active, which was the source of the dendritic grain growth. In contrast, in the D-Gal-0.2 electrolyte, the current quickly reached a steady state, which means that all nucleation sites were rapidly activated and Zn 2+ It is uniformly deposited on the surface of zinc anode by three-dimensional diffusion.
[0053] Embodiment 5:
[0054] ZS and D-Gal-0.2 electrolyte in Example 1.
[0055] Test results see Figure 5 The linear polarization curve (Tafel) curve shows that D-Gal-0.2 has a higher positive corrosion potential (-0.041 V) and a lower corrosion current (-2.956 mA cm -2 ) demonstrated the contribution of D-Gal adsorption to the corrosion resistance of Zn anode.
[0056] Embodiment 6:
[0057] ZS and D-Gal-0.2 electrolyte in Example 1.
[0058] At 1 mA cm -2 and 1 mAh cm -2 Under the conditions of , the pH value of the electrolyte during the deposition / stripping process of Zn||Zn battery was in situ monitored.
[0059] Test results see Figure 6 and Figure 7. The pH value of the ZS electrolyte fluctuated periodically after 10 hours. The increase in pH indicated that a strong HER reaction occurred on the Zn anode surface. Surprisingly, the D-Gal additive had a significant inhibitory effect on the pH fluctuation, and the pH value in the D-Gal-0.2 electrolyte was relatively stable. Obviously, the D-gal additive can change the solvation structure of zinc ions, hinder the decomposition of solvated water, and stabilize the pH value at the electrode / electrolyte interface.
[0060] Embodiment 7:
[0061] ZS and D-Gal-0.2 electrolyte in Example 1.
[0062] Test results see Figure 8 DFT calculations show that the LUMO energy of D-Gal is lower than that of H2O, which indicates that D-Gal is more likely to acquire electrons, thereby effectively suppressing the decomposition of H2O.
[0063] Embodiment 8:
[0064] ZS, D-Gal-10, D-Gal-50, D-Gal-0.2 and D-Gal-0.5 electrolytes in Example 1.
[0065] Test results see Fig. 9 . Button cell tests were performed to assemble Zn||Zn symmetric cells, using ZS, D-Gal-10, D-Gal-50, D-Gal-0.2 and D-Gal-0.5 electrolytes, respectively, and electrochemical impedance spectroscopy (EIS) was used to study the electrolyte-electrode interface state. Among all electrolytes, the symmetric cell in D-Gal-0.2 has the lowest charge transfer resistance (Rct), indicating that the interfacial kinetic stability of the cell is the best as the content of D-Gal additive increases.
[0066] Embodiment 9:
[0067] ZS and D-Gal-0.2 electrolyte in Example 1.
[0068] The button cell test was conducted, and a Zn||Zn symmetrical cell was assembled. ZS and D-Gal-0.2 electrolytes were used respectively. The zinc negative electrode after 25 cycles of deposition was washed with deionized water, dried, and the zinc foil surface was analyzed by XRD. The test results are shown in Fig.10 After cycling in ZS, a large amount of Zn4SO4(OH)6·xH2O hydrogen evolution byproduct appeared on the surface of zinc foil. However, no byproduct appeared on the surface of zinc foil after cycling in D-Gal-0.2. The above results show that hydrogen evolution corrosion of zinc is greatly suppressed in D-Gal-0.2 electrolyte.
[0069] Embodiment 10:
[0070] ZS and D-Gal-0.2 electrolyte in Example 1.
[0071] The Zn||Zn symmetric cell was assembled and the zinc negative electrode deposition process was monitored using in situ optical microscopy. Fig.11 , the surface of the zinc anode in the ZS electrolyte is uneven, with many zinc lumps of different sizes on the surface. Fig.11 In the D-Gal-0.2 electrolyte shown in b, the zinc deposited on the zinc anode surface exhibits a dense and uniform deposition morphology, further demonstrating the efficacy of the D-Gal regulator in uniformly depositing zinc.
[0072] Embodiment 11:
[0073] In Example 1, ZS, D-Gal-10, D-Gal-50, D-Gal-0.2 and D-Gal-0.5 electrolytes are electrolytes.
[0074] Five electrolytes were used to assemble Zn||Cu half-cells at 2 mA cm -2 , 1 mAh cm -2 Under these conditions, the Coulomb efficiency was tested.
[0075] Test results see Fig.12 Compared with the traditional ZS electrolyte, D-Gal-0.2 showed no obvious fluctuation after nearly 2,300 electroplating / stripping cycles, while ZS and other concentrations of D-Gal electrolytes showed severe short-circuit fluctuations in less than 300 cycles. This shows that the stability of the zinc negative electrode is greatly improved due to the improvement of zinc deposition morphology and the inhibition of hydrogen evolution corrosion by D-Gal-0.2.
[0076] Embodiment 12:
[0077] In Example 1, ZS, D-Gal-10, D-Gal-50, D-Gal-0.2 and D-Gal-0.5 electrolytes are electrolytes.
[0078] Test results see Fig.13 Compared with ZS electrolyte, the stable cycle time of Zn||Zn symmetric battery with D-Gal-0.2 electrolyte is significantly improved. This shows that the stability of zinc negative electrode is greatly improved due to the improvement of zinc deposition morphology and the inhibition of hydrogen evolution corrosion by Zn||Zn mixed electrolyte.
[0079] Embodiment 13:
[0080] D-Gal-0.2 electrolyte in Example 1.
[0081] Preparation of ZVO cathode material: First, 360.0 mg V2O5 powder and 74.0 mg Zn(NO3)2·6H2O were dissolved in 30 mL deionized water and stirred continuously for 10 min. The Zn(NO3)2·6H2O solution was transferred to the V2O5 suspension, and then 2.0 mL 30 vol % H2O2 was added and stirred for 30 min. The resulting transparent orange solution was transferred to a 100 mL polytetrafluoroethylene autoclave and heated at 120 °C for 12 h. Finally, the solid precipitate Zn x V2O5·X H2O(ZVO) was then collected by centrifugation with ethanol and deionized water several times and dried by freeze drying process. A well-mixed slurry (mass ratio of 7:2:1) containing ZVO powder, conductive carbon (Super P) and polyvinylidene fluoride (PVDF) binder was cast on Ti foil (diameter: 12 mm) to make ZVO cathode. The prepared electrode was dried in a vacuum oven at 60 °C for 10 h.
[0082] Battery assembly: Using the D-Gal-0.2 electrolyte in Example 1, Zn||ZVO soft pack batteries were assembled at 1 A g -1 Perform charge and discharge tests for the test conditions.
[0083] Test results see Fig.14 The Zn||ZVO full cell with D-Gal-0.2 retains a capacity of 100 mAh g after 200 cycles at a loading of 1.56 mg. -1 The above shows that D-Gal-0.2 electrolyte can achieve stable circulation of zinc negative electrode under full battery conditions. The illustration shows that the soft pack battery using D-Gal-0.2 electrolyte lights up the light bulb, indicating that D-Gal-0.2 electrolyte has practical application value.
Claims
1. An aqueous zinc ion battery electrolyte, characterized in that: The electrolyte includes a zinc salt and a solvent, and the solvent includes water and D-Gal.
2. The electrolyte according to claim 1, characterized in that The molar concentration of D-Gal in the solution is 0-0.5M.
3. The electrolyte according to claim 1, characterized in that The zinc salt is any one of zinc sulfate, zinc chloride, zinc nitrate, zinc acetate, zinc phosphate, zinc trifluoromethanesulfonate, zinc bistrifluoromethanesulfonyl imide, zinc tetrafluoroborate, zinc hexafluorophosphate, and zinc bisoxalate borate, or a combination of at least two thereof.
4. The electrolyte according to claim 3, characterized in that The zinc salt is zinc sulfate.
5. The electrolyte according to claim 1, characterized in that The concentration of the zinc salt in the electrolyte is 2 mol / L.
6. An aqueous zinc ion battery, characterized in that: The aqueous zinc ion battery comprises the electrolyte according to any one of claims 1 to 5.
7. The zinc ion battery according to claim 6, characterized in that: The zinc ion battery comprises a positive electrode, a membrane and a zinc negative electrode; the positive electrode is made of a zinc ion embedding and releasing material, and the zinc ion embedding and releasing material is a manganese-based material, a vanadium-based material or a combination thereof; the manganese-based material is MnO2, Ca 0.28 The vanadium-based material is one or more of V2O5, V2O3, Zn2V2O7 and KV3O8; the membrane is a glass fiber membrane or a Celgard membrane; the zinc negative electrode is zinc foil or zinc powder.
8. The zinc ion battery according to claim 7, characterized in that: The positive electrode is Zn x V2O5·H2O (ZVO) and VO2-D; the membrane is a glass fiber membrane; the zinc negative electrode is zinc foil.
